Perspective on the Role of Antibodies and Potential Therapeutic Drugs to Combat COVID-19 - Tandon, Siddhi (Protein J, 2020)
The sudden emergence of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing the coronavirus disease of 2019 (COVID-19) has brought the world to a standstill. Thousands of people across the globe are biting the dust with every passing day and yet more are being tested positive for the SARS-CoV-2 infection. In order to dispense this current crisis, numerous treatment options have been tried and tested and many more are still under scrutiny. The development of vaccines may help in the prevention of the global pandemic, however, there is still a need for the development of alternate approaches to combat the disease. In this review we highlight the new discoveries and furtherance in the antibody based therapeutic options and the potent drugs, with special emphasis on the development of the monoclonal and polyclonal antibodies and the repurposed drugs, which may prove to be of significant importance for the treatment of COVID-19, in the days to come. It is an attempt to evaluate the currently presented challenges so as to provide a scope for the ongoing research and assistance in the development of the effective therapeutic options against SARS-CoV-2. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10930-020-09921-0) contains supplementary material, which is available to authorized users.